2011
DOI: 10.2190/de.41.4.e
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Web-Based, Tailored, Alcohol Prevention/Intervention Program for College Students: 3-Month Follow-up

Abstract: This study presents the results of an efficacy evaluation of a Web-based brief motivational alcohol prevention/intervention program called Michigan Prevention and Alcohol Safety for Students (M-PASS). Four on-line sessions providing individually-tailored feedback were delivered to first-year college students over nine weeks. Non- and low-risk drinking participants received risk prevention, while high-risk drinking participants received a risk-reduction intervention. Both intervention and control groups were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Other prevalent settings included military/army (n = 11, 11%) [52, 60, 61, 69, 71, 72, 104, 110, 119, 127, 128] and internet (n = 8, 8%) [45, 85, 92, 113, 132, 139, 148, 149]. Five studies (5%) were delivered in multiple settings [83, 111, 120, 122, 145].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other prevalent settings included military/army (n = 11, 11%) [52, 60, 61, 69, 71, 72, 104, 110, 119, 127, 128] and internet (n = 8, 8%) [45, 85, 92, 113, 132, 139, 148, 149]. Five studies (5%) were delivered in multiple settings [83, 111, 120, 122, 145].…”
Section: Resultsmentioning
confidence: 99%
“…Other modes included online (n = 8, 8%) [45, 52, 85, 113, 132, 139, 148, 149], paper (n = 5, 5%) [137, 138, 140, 142, 143], TV/video/DVD (n = 2, 2%) [92, 93] and a social marketing campaign (n = 1, 1%) [106]. Many studies (n = 13, 13%) implemented multi-faceted intervention modes [59, 83, 95, 111, 115, 116, 118120, 122, 131, 141, 145].…”
Section: Resultsmentioning
confidence: 99%
“…25 Conclusions regarding BIs efficacy vary based on substance, problem severity, setting, and delivery mechanism. For example, a universal prevention focused, computerized, alcohol BI among college freshman showed greater effects for non-drinkers than low risk drinkers; 30 however, other studies have found greater effects for selective or indicated prevention samples (substance users) than universal prevention samples. 43 Further, a recent review concluded TBIs were more effective than CBIs among college students who misused alcohol.…”
Section: Discussionmentioning
confidence: 96%
“…Although such studies are lacking among adolescents in primary care, among adolescents in the ED 29 and college students, 30,31 universal prevention focused, computer delivered alcohol BIs are effective in the short term and/or with at-risk subgroups of participants. A prior manuscript from the study described in this paper examining cannabis users showed that a selective computer BI decreased other drug use and cannabis-related consequences but not cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…Most provide information to improve knowledge about substance use as well as interactive activities or videos that provide opportunities for participants to practice skills. In general, Web-based prevention programs were found to be more effective with youth at higher risk for alcohol abuse (Bingham et al 2011;Moore et al 2005;Doumas and Andersen 2009;Neighbors et al 2010).…”
Section: Web-based and Web-enhanced Technologiesmentioning
confidence: 99%